2020
DOI: 10.1177/1559325820902314
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Hybridized With Gadolinium(III) Nanoplatform for Targeted Magnetic Imaging–Guided Photothermal Breast Cancer Therapy

Abstract: Achieving drug target accumulation in antitumor tissue, simultaneous diagnostic imaging, and optimal release behavior with treatment needs a best chemotherapy procedure involving receptive switch of drug delivery. Constructed on mesoporous silica nanoparticles, which are crossed with multiscale charming nanoparticles for magnetic resonance imaging (MRI)-aided and alternate magnetic field (AMF) response chemotherapy for breast cancer, we report in this work the assembly of a new theranostics drug conveyance pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…As-prepared contrast materials were injected into healthy SD rats for in-vivo imaging to evaluate Gd 2 O 3 @MSN as an in-vivo MRI contrast agent. Previous studies have shown that MSN adsorbs plasma proteins and interacts strongly with the tissue-resident macrophages in the mononuclear phagocyte system (MPS), leading to rapid blood clearance and accumulation in the liver and spleen ( Gao et al, 2011 ; Ekkapongpisit et al, 2012 ; Li et al, 2016 ; Wang and Sun, 2020 ). Given this, we used the likely accumulation of our NPs in the hepatic Kupffer cells to determine our ROIs, focusing on the liver region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As-prepared contrast materials were injected into healthy SD rats for in-vivo imaging to evaluate Gd 2 O 3 @MSN as an in-vivo MRI contrast agent. Previous studies have shown that MSN adsorbs plasma proteins and interacts strongly with the tissue-resident macrophages in the mononuclear phagocyte system (MPS), leading to rapid blood clearance and accumulation in the liver and spleen ( Gao et al, 2011 ; Ekkapongpisit et al, 2012 ; Li et al, 2016 ; Wang and Sun, 2020 ). Given this, we used the likely accumulation of our NPs in the hepatic Kupffer cells to determine our ROIs, focusing on the liver region.…”
Section: Resultsmentioning
confidence: 99%
“…These NDDS combine a therapeutic payload with nano-sized carriers (such as liposomes, gold nanoparticles, polymeric micelles, and mesoporous silica) to reduce side effects and prolong circulation time ( Mikada et al, 2017 ; Layek et al, 2020 ). Thus, the introduction of MRI contrast agents into an NDDS may both extend blood circulation time and improve MRI performance (because of the shortened longitudinal proton relaxation time of the surrounding water molecules for T 1 -type contrast agents) ( Lin et al, 2004 ; Parvesh et al, 2012 ; Li et al, 2014 ; Hu et al, 2015 ; Deng et al, 2016 ; Wang and Sun, 2020 ). Of the common NDDS carriers mesoporous silica nanoparticles (MSNs) are widely used in the carriers for drug delivery and biosensing and are likely to be the most appropriate carrier for gadolinium owing to their high surface area, ease of preparation, good biocompatibility, and mesoporous structure ( Lin et al, 2004 ; Taylor et al, 2008 ; Xia et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…To examine the effect of photothermal conversion of CaF 2 :Y,Nd NPs under laser irradiation, real-time thermograms and temperature changes after irradiation were recorded using an infrared thermographer (Fluke Ti32, Fluke Corporation, USA) [33][34][35][36]. Specifically, 100 μg/mL of CaF 2 :Y,Nd NPs and saline (control) were stored in a 12-well plate.…”
Section: Infrared Thermal Imagingmentioning
confidence: 99%